PLAYING MUSIC, CREATING THE FUTURE: EXPLORING CARDBOARD MEDIA IN DAYAK MUSICAL INSTRUMENT LEARNING - Mastri Dihita Sagala (Sanata Dharma University Yogyakarta, 2026)
The limited access to traditional Dayak musical instruments, the Dau', drives innovation in music learning in the digital era. This research explores students' perceptions of using cardboard media as a creative alternative in learning the basics of the instrument. Through a qualitative approach, this study found that students responded positively to the cardboard media. Data were collected through participant observation, documentation, and interviews with the 2023 cohort of Performing Arts Education students at Tanjungpura University. Open-ended questions were used to understand how students perceive the cardboard media used in the learning process. Data analysis used triangulation techniques to understand students' opinions regarding the learning media. The research results show that students have a positive view of using cardboard media in the basic music learning of the Dayak. They assess that this media is not only effective in facilitating the understanding of Dayak music concepts but also stimulates creativity and fine motor skills. These findings indicate that cardboard media can be an innovative and flexible solution in traditional music education, especially in resource-limited environments. The implications of this research open up opportunities for further development, such as the integration of augmented reality technology, to create a more immersive and engaging learning experience for the millennial generation.